2021
DOI: 10.32473/edis-fe1110-2021
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' Perceptions and Preferences toward Florida Orange Juice

Abstract: Faced with reduced domestic supply, competition from imports, and high production costs, the Florida citrus industry and Florida growers need to understand how consumers perceive Florida-produced orange juice and whether they value it more than OJ produced elsewhere. We conducted a national survey to understand consumers' perceptions and confirmed that consumers have a superior perception of Florida OJ, which could lead to higher rates of willingness-to-buy and willingness-to-pay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
3
1
0
4
Order By: Relevance
“…We found that consistency, price, taste, brand, and health/nutritional benefits are the most important factors when purchasing OJ, conforming to previous results from Heng, House, et al (2021). The strong preference for domestic OJ is also in line with other studies that document a growing demand for “local” foods (Arnoult et al, 2007; Costanigro et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…We found that consistency, price, taste, brand, and health/nutritional benefits are the most important factors when purchasing OJ, conforming to previous results from Heng, House, et al (2021). The strong preference for domestic OJ is also in line with other studies that document a growing demand for “local” foods (Arnoult et al, 2007; Costanigro et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…This preference is also manifested in the positive WTP for Florida OJ from the mixed logit model. This conforms with Heng, House, et al (2021), who showed a strong preference for Florida OJ, mainly for better taste and quality, and an interest in supporting local farmers. This result is reassuring for the Florida citrus industry, especially given current production issues caused by citrus greening.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although consumers have stated their preference for orange juice from Florida, and many believe that their currently purchased orange juice is from Florida (Heng, House, and Yoon, 2021), it remains a question whether orange juice consumers are willing to pay more for orange juice labeled "Florida." Therefore, this study aims to answer the question with four objectives: (1) identify the proportion of consumers who perceive Florida orange juice as superior to other orange juice; (2) explore demand drivers behind orange juice and orange juice labeled "Florida," (3) investigate consumer willingness-to-pay (WTP) a premium for Florida orange juice; and (4) identify individual characteristics affecting for different levels of Florida oranges.…”
Section: Introductionmentioning
confidence: 99%
“…Konsumen menilai suatu produk melalui atribut-atribut tersebut. Pada akhirnya, konsumen akan mengambil keputusan pembelian berdasarkan preferensinya terhadap suatu produk tertentu (Heng, House, & Yoon, 2021).…”
unclassified